2021
DOI: 10.1021/acssensors.0c02561
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Magneto Immunosensor for Rapid, High Sensitivity Measurements of SARS-CoV-2 Nucleocapsid Protein in Serum

Abstract: The COVID-19 pandemic has highlighted the importance and urgent need for rapid and accurate diagnostic tests for COVID-19 detection and screening. The objective of this work was to develop a simple immunosensor for rapid and high sensitivity measurements of SARS-CoV-2 nucleocapsid protein in serum. This assay is based on a unique sensing scheme utilizing duallylabeled magnetic nanobeads for immunomagnetic enrichment and signal amplification. This immunosensor is integrated onto a microfluidic chip, which offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 29 publications
2
119
0
Order By: Relevance
“…Th manufacturer of the antibody used in this study (Sino Biological) has also reported cross reactivity with SARS-CoV. This cross reactivity has been previously reported for all the immunoassays using the N protein [29]. However, we believe that this cross reactivity does not have an impact on the current COVID 19 diagnosis because there are no new reported SARS-CoV outbreaks since 2004 [40].…”
Section: Selectivity Of the Sars-cov-2 Immunosensorsupporting
confidence: 58%
See 2 more Smart Citations
“…Th manufacturer of the antibody used in this study (Sino Biological) has also reported cross reactivity with SARS-CoV. This cross reactivity has been previously reported for all the immunoassays using the N protein [29]. However, we believe that this cross reactivity does not have an impact on the current COVID 19 diagnosis because there are no new reported SARS-CoV outbreaks since 2004 [40].…”
Section: Selectivity Of the Sars-cov-2 Immunosensorsupporting
confidence: 58%
“…It is worth noting that the immunosensor is easier to use compared with the other biosensors that needs an extraction step for the RNA [23,24]. Moreover, the LOD of the SARS-CoV-2 N protein immunosensor was lower than all the other reported electrochemical biosensors for the same protein [28][29][30][31] as shown in Table 1.…”
Section: Dose Response Of the Sars-cov-2 Immunosensormentioning
confidence: 95%
See 1 more Smart Citation
“…: Example of smartphone tool using magnetic nanobeads in a microfludic immunosensor 339 which can detect SARS-CoV-2 nucleocapsid (N) protein in serum. The requirement for serum decreases its appeal as a tool for mass deployment.…”
Section: Figure 23bmentioning
confidence: 99%
“…Figure 23b: Example of smartphone tool using magnetic nanobeads in a microfludic immunosensor 339 which can detect SARS-CoV-2 nucleocapsid (N) protein in serum. The requirement for serum decreases its appeal as a tool for mass deployment.…”
Section: Post-pandemic Public Health and Healthcare: Broad Spectrum Use Of Sensors With Smartphonesmentioning
confidence: 99%